First Travel Fraud Case and the Legal Protection for the Victims - Siraji, Hafizh (Faculty of Law Universitas Negeri Semarang, 2021)
Fraud committed by PT. First Travel has at least harmed prospective Hajj and Umrah pilgrims as many as 35,000 people, of which the material loss in this case is 500 billion. This is also suspected by the lack of strict regulations made by the state through Law No. 13 of 2008 concerning the implementation of Hajj and Umrah. However, until now the protection for the loss of first travel victims has not been completed, the decision of the Depok District Court with case number 83/Pid.B/2018/PN.Dpk which led to an appeal with case number 3096/K/PID.SUS/2018 decided on January 31, 2019. All assets seized were in accordance with the Decree of the Minister of Justice of the Republic of Indonesia Number M.04.PR.07.03 of 1985 concerning the organization and working procedures of RUTAN and RUPBASAN. This paper is indented to analyze the protection for the victims on the fraud case on PT First Travel Fraud case.